Comprehensive Genomic Characterization of the NAC Transcription Factors and Their Response to Drought Stress in Dendrobium catenatum - Yuxin Li; Tingting Zhang; Wenting Xing; Jian Wang; Wengang Yu; Yang Zhou (Agronomy, 2022)
As a large transcription factor family, NAC family proteins (NAM, ATAF1,2, and CUC2) play critical roles in plant growth, development, and response to stresses. Herein, the NAC gene family of Dendrobium catenatum was identified and analyzed by bioinformatics methods. Their expression patterns in different tissues and under drought stress were analyzed using RNA-seq data and the quantitative real-time reverse transcription-polymerase chain reaction (RT-qPCR) method. A total of 90 NAC genes were identified, encoding amino acids with numbers ranging from 88 to 1065, with protein molecular weight ranging from 10.34 to 119.24 kD, and isoelectric point ranging from 4.5 to 9.99. Phylogenetic analysis showed that the DcNAC proteins could be divided into 17 subgroups, and each subgroup had conserved motif composition and gene structure. Twenty types of cis-elements were identified in the DcNAC promoters. RNA-seq analysis showed that the expression of DcNAC genes had tissue specificity and displayed different expression patterns under drought stress. Co-expression network analysis of the DcNAC genes revealed nine hub genes, and their expression levels were then validated by RT-qPCR. The results showed that DcNAC6, DcNAC18, DcNAC29, DcNAC44, and DcNAC51 (mainly in roots) as well as DcNAC16 and DcNAC64 (mainly in leaves) were considered as the candidate genes for drought tolerance in D. catenatum. Taken together, this study identified candidate NAC genes with potential functions in response to drought stress, which is valuable for development of drought resistance in D. catenatum.